La médicalisation de la maternité au Québec, 1910-1970: autour de la notion de risque - Baillargeon, Denyse (Une démographie au féminin: risques et opportunités dans le parcours de vie / A Female Demography: Risks and Chances in the Life Course, 2009)
Keywords: Femmes; Médecine

La médicalisation de la maternité au Québec comme enjeu de pouvoir (1910-1970) - Baillargeon, Denyse (Pouvoir médical et santé totalitaire: conséquences socio-anthropologiques et éthiques, 2009)
Keywords: Femmes; Médecine

Maternidad y migración: Entre recuerdos y pensares: Historias de vida de quince mujeres latinoamericanas que habitan en Montréal (Canadá) - Bedoya Idrobo, Luz Marina (Université de Montréal, 2009)
Keywords: Femmes; Latino-Américains

J’haïs les féministes. Le 6 décembre 1989 et ses suites - Blais, Mélissa (Les éditions du remue-ménage, 2009)
Keywords: Commémoration; Femmes; Féminisme; École polytechnique

Autorité, genre et expertise: le cas de l’assistance catholique à Montréal - Bourbeau, Amélie (Revue d'histoire de l'Amérique française, 2009)
Keywords: Federation of Catholic Charities (FCC); Fédération des œuvres de charités canadiennes-françaises (FOCCF)

Class, Gender, and the Social Standard: The Montreal Junior League, 1912–1939 - Chenier, Elise (Canadian Historical Review, 2009)
Keywords: Anglophones; Bourgeoisie; Femmes

Un discours masculin sur la société: la publicité dans les quotidiens québécois des années 1920 aux années 1960 - Couvrette, Sébastien (Université du Québec à Montréal, 2009)
Keywords: Devoir (Le); Montreal Star; Presse (La); Publicité

"Bonifier le capital humain". Le genre dans le discours médical et religieux sur les sports au Québec, 1920-1950 - Detellier, Élise (Revue d'histoire de l'Amérique française, 2009)

"Au-delà des apparences: le corps investi par le voile": discours, représentations et pratiques de femmes musulmanes originaires de l'Iran, du Maroc et de la Tunisie ayant immigré à Montréal - Gagné, Isabelle (Université Laval, 2009)
Keywords: Iraniens; Maghrébins; Marocains; Musulmans; Tunisiens

Elsie Reford, une bourgeoise montréalaise et métissienne. Un exemple de spatialisation des sphères privée et publique - Hébert, Karine (Revue d'histoire de l'Amérique française, 2009)
Keywords: Bourgeoisie

William Notman’s Portrait Photographs of the Wealthy English-speaking Girls of Montreal: Representations of Informal Female Education in Relation to John Ruskin’s “Of Queens’ Gardens” and Writings by and for Canadians from the 1850s to 1890s - Lerner, Loren Ruth (Revue d'histoire de l'éducation / Historical Studies in Education, 2009)
Keywords: Bourgeoisie; Femmes

Éva Circé-Côté, journaliste montréalaise au-delà de la singularité - Lévesque, Andrée (Interrelations femmes-médias dans l'Amérique française, 2009)
Keywords: Circé-Côté, Éva; Journalistes

Les Midinettes de 1937: culture ouvrière, culture de genre, culture ethnique - Lévesque, Andrée (1937: un tournant culturel, 2009)
Keywords: Confection; Femmes; Syndicats internationaux; Union internationale des ouvriers du vêtement pour dames

One (Wo)man’s Shopping is the Same (Wo)man’s history? Immigration, Advertisement and Consumption Patterns in the Greek community of Montreal 1960s-1970s - Pabst, Stavroula (Études canadiennes / Canadian Studies, 2009)
Keywords: Femmes; Grecs; Publicité

La légitimité incertaine des travailleuses du sexe dans le mouvement des femmes au Québec - Toupin, Louise (Globe: revue internationale d'études québécoises, 2009)
Keywords: Femmes; Prostitution

Les femmes et la politique dans les caricatures de Robert La Palme, 1943-1951 - Turgeon, Alexandre (Revue d'histoire de l'Amérique française, 2009)
Keywords: Caricature; Femmes

Femmes et sikhisme à Montréal: le cas des représentations des femmes et des rapports homme-femme - Vig, Julie (Université du Québec à Montréal, 2009)
Keywords: Femmes; Indiens

Un parti pris sexuel. Sexualité et masculinité dans la Revue Parti Pris - Warren, Jean-Philippe (Globe: revue internationale d’études québécoises, 2009)
Keywords: Parti Pris

Working for Pay and Managing the Household - Baillargeon, Denyse (Labouring Canada: Class, Race, and Gender in Canadian History, 2008)
Keywords: Femmes; Travail

Pratiques et stratégies d'appropriation spatiale des groupes de femmes montréalais - Bêchard, Clotilde (Université du Québec à Montréal, 2008)
Keywords: Femmes

Divided by the Ballot Box: The Montreal Council of Women and the 1917 Election - Brookfield, Tarah (Canadian Historical Review, 2008)
Keywords: Femmes; Féminisme; Montreal Local Council of Women; Élections

Homosexualités: perspectives historico-politiques - Chamberland, Line (Bulletin d'histoire politique, 2008)

La représentation de l'héroïne dans les romans historiques québécois (1945-1995) ayant comme trame de fond la Nouvelle-France. Les femmes en trois actes: l'épouse, la mère et la veuve - Gingras, Marie-Ève (Université de Sherbrooke, 2008)
Keywords: Femmes; Roman

Les liens associatifs des femmes chiliennes - Grabowiecka, Marie-Sophia (Université du Québec à Montréal, 2008)
Keywords: Chiliens; Femmes; Féminisme

Culture et conflit intergénérationnel dans la famille cambodgienne à Montréal: les récits des mères - Khai, Sophearath (Université du Québec à Montréal, 2008)
Keywords: Cambodgiens; Famille; Femmes

Les représentations de la femme dans l’œuvre scénique de Diane Dufresne, 1975-1984 - Lafrenière, Marilyne (Université du Québec à Trois-Rivières, 2008)
Keywords: Chanson; Musique

Les premiers mouvements féministes au Québec, 1893-1940 - Leclerc, Johannie (Université de Sherbrooke, 2008)
Keywords: Féminisme

The Conservation of a Gender Fantasy: Women and Top 40 Radio in Montreal - Maki, Christine (Université McGill, 2008)
Keywords: Femmes; Radio

Une voix féminine dans l’espace public. La Galerie Dominion, 1941-1956 - Pageot, Édith-Anne (Globe: revue internationale d'études québécoises, 2008)
Keywords: Femmes; Peinture

Représentations des immigrantes roumaines sur leurs usages d'internet en contexte d'immigration à Montréal - Regus, Oriane (Université du Québec à Montréal, 2008)
Keywords: Femmes; Internet; Roumains

Influence de la presse écrite sur l'émancipation de la communauté gaie montréalaise au XXe siècle - Roberge, Jean-François (Université du Québec à Montréal, 2008)

Femmes, ethnicité et religion: la communauté tamoule hindoue du Sri Lanka à Montréal - St-Germain Lefebvre, Catherine (Université du Québec à Montréal, 2008)
Keywords: Femmes; Sri Lankais

Entre la folie d'un seul homme et les violences faites aux femmes: la mémoire collective entourant les événements de la tuerie du 6 décembre 1989 - Blais, Mélissa (Université du Québec à Montréal, 2007)
Keywords: Commémoration; Femmes; Féminisme; École polytechnique

La question du travail domestique au début du XXe siècle au Québec: un enjeu à la Fédération nationale Saint-Jean-Baptiste, 1900-1927 - Charron, Catherine (Université Laval, 2007)
Keywords: Fédération nationale Saint-Jean-Baptiste; Travail

Jeunes femmes et loisirs commerciaux durant les années folles (1919-1929): Étude des discours ecclésiastiques et journalistiques - Comtois, Patricia (Université du Québec à Montréal, 2007)
Keywords: Femmes; Patin; Ski

La place des femmes dans la Société d'art contemporain: Montréal, 1939-1948 - Fortin, Nathalie (Université du Québec à Montréal, 2007)
Keywords: Femmes; Société d'art contemporain

Elsie Reford, au-delà des jardins - Hébert, Karine (Elsie: une œuvre hommage de Dominique Blain / Elsie: a Tribute by Dominique Blain, 2007)
Keywords: Bourgeoisie

La représentation et le traitement du débat entourant le mariage homosexuel par Le Devoir et La Presse (2003-2005) - Patino Martinez, Jaime Salvador (Université du Québec à Montréal, 2007)
Keywords: Devoir (Le); Mariage; Presse (La)

"It's Funny the Things You Remember": Memories of Gendered Childhood in Montreal during the Great Depression - Rebelo, Nancy Moniz (Université Concordia, 2007)
Keywords: Crise; Enfants

La représentation féminine dans le contenu publicitaire de La Presse et Le Devoir pendant la Seconde Guerre mondiale (1939-1945): deux visions opposées - Roy, Stéphanie (Université de Sherbrooke, 2007)
Keywords: Devoir (Le); Femmes; Guerre; Presse (La); Publicité

Indispensable but not a Citizen: the Housewife in the Great Depression - Baillargeon, Denyse (Rethinking Canada: the Promise of Women's History, 2006)
Keywords: Crise; Famille; Femmes

L'histoire des Montréalaises: un chantier en construction - Baillargeon, Denyse (Vivre en ville. Bruxelles et Montréal aux XIXe et XXe siècles, 2006)
Keywords: Femmes; Histoire

Genre, religion et politiques sociales au Québec dans les années 1930. Les pensions aux mères - Cohen, Yolande (Revue canadienne de politique sociale, 2006)
Keywords: Famille; Femmes

Les femmes et la ville en temps de guerre et en temps de paix. Montréal dans les années 1940 - Fahrni, Magda (Vivre en ville. Bruxelles et Montréal aux XIXe et XXe siècles, 2006)
Keywords: Femmes; Guerre

Remarking Waves: The Quebec Women's Movement in the 1950s and the 1960s - Gosselin, Cheryl (Canadian Woman Studies / Les Cahiers de la femme, 2006)
Keywords: Femmes

A Home away from Home: Defining, Regulating, and Challenging Femininity at the Julia Drummond Residence in Montreal, 1920–1971 - Kirkland, Elizabeth (Urban History Review / Revue d'histoire urbaine, 2006)
Keywords: Femmes; Logement

De colombine à Julien Saint-Michel: le féminisme chez Éva Circé-Côté (1900-1921) - Létourneau, Émilie (Université de Sherbrooke, 2006)
Keywords: Circé-Côté, Éva; Féminisme; Journalistes

Jeunesse, tu deviendras homme. Les discours identitaires véhiculés au sein de l'Association Catholique de la jeunesse canadienne-française, 1904-1931 - Manseau, Caroline (Université de Sherbrooke, 2006)
Keywords: Association catholique de la jeunesse canadienne-française (ACJC)

L’idéal maternel: discours, représentation et célébration des mères québécoises à l’occasion de la fête des mères, 1940-1980 - Marando, Nancy (Université de Montréal, 2006)
Keywords: Enfants; Famille; Femmes; Montreal Star; Presse (La)

Évolution du discours féministe sur "la prostitution" au Québec - Mensah, Maria Nengeh; Laberge, Marie-Claude (Bulletin d'histoire politique, 2006)
Keywords: Féminisme; Prostitution

Débat féministe sur la prostitution au Québec: points de vue des travailleuses du sexe - Mensah, Marie Nengeh (Canadian Review of Sociology / Revue canadienne de sociologie, 2006)
Keywords: Féminisme; Prostitution

Les représentations de la féminité et de la masculinité à travers le thème des rapports amoureux dans la chanson populaire francophone consommée au Québec, 1960-1990 - Ouellette, Myrthô (Université de Sherbrooke, 2006)
Keywords: Chanson; Musique

Sur la légèreté d'être gaie ou les constructions discursives du sport, du genre et de la sexualité chez les jeunes sportives de Montréal - Ravel, Barbara (Université de Montréal, 2006)

Les règles du jeu de la séduction dans les manuels de savoir-vivre québécois (1863-1917): investir le monde du sentiment et de l’intimité masculine - Roy, Sonya (Université de Montréal, 2006)
Keywords: Bourgeoisie; Mariage

Fréquentations et mariage, les représentations de jeunes québécoises à travers l'étude d'un courrier du coeur (1958-1968) - Sénéchal, Johanne (Université Laval, 2006)
Keywords: Bertrand, Janette; Femmes; Mariage

Forme urbaine, comportements de localisation et mobilité quotidienne - Vandersmissen, Marie-Hélène (Cahiers de géographie du Québec, 2006)

Embodying Delinquency: Boys’ Bodies, Sexuality, and Juvenile Justice History in Early Twentieth-Century Quebec - Myers, Tamara (Journal of the History of Sexuality, 2005)
Keywords: Délinquance; Enfants; Tribunaux

Identité ethnique et identité érotique: le cas de lesbiennes d'origine haïtienne - Ambrosi, Sophie (Université de Montréal, 2005)
Keywords: Femmes; Haïtiens

Bending the Rules: The Montreal Branch of the Woman's Art Association of Canada, 1894-1900 - Haskins, Victoria (Université Concordia, 2005)
Keywords: Art association; Femmes

The Women's Movement in Canada: Setting the Agenda - Kaye, Lynn; McDonald, Lynn (Madeleine Parent: Activist, 2005)
Keywords: Femmes; Féminisme; Parent, Madeleine

Permeable Boundaries: Negotiation, Resistance, and Transgression of Street Space in Saint-Henri, Quebec, 1875-1905 - Lord, Kathleen (Urban History Review / Revue d'histoire urbaine, 2005)
Keywords: Quartiers; Rues; Saint-Henri

Perspectives féminines sur les hommes et le couple. Châtelaine, 1960-1975 - Malo, Isabelle (Université de Montréal, 2005)
Keywords: Femmes

Étude de cas. Joséphine Marchand-Dandurand: la lecture au féminin - Montreuil, Sophie (Histoire du livre et de l'imprimé au Canada, vol. II (1840-1918), 2005)
Keywords: Femmes; Marchand-Dandurand, Joséphine

The Importance of Being Madeleine: How an Activist Won the Hearts of Quebec's Immigrant and Minority Women - Mulay, Shree (Madeleine Parent: Activist, 2005)
Keywords: Parent, Madeleine

On Probation: The Rise and Fall of Jewish Women's Antidelinquency Work in Interwar Montreal - Myers, Tamara (Negotiating Identities in 19th- and 20th- Century Montreal, 2005)
Keywords: Délinquance; Femmes; Juifs

Regulation, Agency, and the Transformation of Care for “Predelinquent” Girls - Myers, Tamara (La régulation sociale entre l’acteur et l’institution. Pour une problématique historique de l’interaction / Agency and Institutions in Social Regulation: Towards an Historical Understanding of Their Interaction, 2005)
Keywords: Délinquance; Enfants

C'était du spectacle!: l'histoire des artistes transsexuelles à Montréal, 1955-1985 - Namaste, Viviane (McGill-Queen's University Press, 2005)
Keywords: Cabarets

A Ritual Transformed: Women Smokers in Montreal, 1888-1950 - Rudy, Jarrett (Negotiating Identities in 19th- and 20th- Century Montreal, 2005)
Keywords: Femmes; Tabac

Un Québec en mal d’enfants: la médicalisation de la maternité, 1910-1970 - Baillargeon, Denyse (Remue-ménage, 2004)
Keywords: Enfants; Femmes

Itineraries of Marriage and Widowhood in Nineteenth-Century Montreal - Bradbury, Bettina (Mapping the Margins: The Family and Social Discipline in Canada, 1700-1975, 2004)
Keywords: Femmes; Mariage; Veuvage

Commercialisation des produits de beauté, pratiques esthétiques et représentations du corps de la femme à Montréal, 1870-1915 - Chartrand, Mélanie (Université de Montréal, 2004)
Keywords: Femmes; Publicité

"S'unir pour être plus fort": le Conseil des femmes membres de la Chambre de commerce du district de Montréal, 1956-1971 - Detellier, Élise (Université de Montréal, 2004)
Keywords: Chambre de commerce; Femmes

Hier ne meurt jamais. Vision et désillusions d'une quête identitaire féminine au Québec. La Bonne Parole, organe de la Fédération nationale Saint-Jean-Baptiste, 1913-1958 - Dornic, Isabelle (Université Laval, 2004)
Keywords: Femmes; Fédération nationale Saint-Jean-Baptiste

"Elles sont partout": Les femmes et la ville en temps d'épidémie. Montréal, 1918-1920 - Fahrni, Magda (Revue d'histoire de l'Amérique française, 2004)
Keywords: Bénévolat; Communautés religieuses; Femmes; Infirmières; Épidémies

Carabines, poutchinettes co-eds ou freschettes sont-elles des étudiantes? Les filles à l’Université McGill et à l’Université de Montréal (1900-1960) - Hébert, Karine (Revue d'histoire de l'Amérique française, 2004)
Keywords: Femmes; Université McGill; Université de Montréal; Étudiants

Du silence à l'affirmation: Women Making History in Point St. Charles - Kruzynski, Anna (Université McGill, 2004)
Keywords: Femmes; Pointe-Saint-Charles; Quartiers

Québécoises Deboutte!: Le Front de libération des femmes du Québec, le Centre des femmes et le nationalisme - Mills, Sean (Mens, 2004)
Keywords: Femmes; Féminisme; Nationalisme

Documentaire interactif Paseo: promenade avec des femmes latino-américaines de Montréal - Rojas Huerta, Ivan (Université du Québec à Montréal, 2004)
Keywords: Femmes; Latino-Américains

Des réseaux en convergence. Les espaces de la sociabilité littéraire au féminin dans la première moitié du XIXe siècle - Roy, Julie (Globe: revue internationale d'études québécoises, 2004)
Keywords: Clubs; Écrivains

Persister et signer: Les signatures féminines et l’évolution de la reconnaissance sociale de l’écrivaine (1893-1929) - Savoie, Chantal (Voix et Images, 2004)
Keywords: Femmes; Journalistes; Écrivains

Faith, Family, Female Education and Friendship: Retelling Louise Amelia Monk's Adolescence in Bourgeois Montreal, 1867-1871 - Brettler Vandervort, Jessica L. (Université Concordia, 2003)
Keywords: Bourgeoisie; Femmes

"Les femmes accélèrent la machine de guerre": le travail des femmes durant la Seconde Guerre mondiale dans Le Monde ouvrier - Detellier, Élise (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2003)
Keywords: Confédération des travailleurs catholiques du Canada (C.T.C.C.); Conseil des métiers et du travail de Montréal; Femmes; Fédération des travailleurs et travailleuses du Québec (FTQ); Guerre

The Interplay between Ethnicity, Religion and Gender among Second-Generation Christian and Muslim Arabs in Montreal - Eid, Paul (Canadian Ethnic Studies / Études ethniques au Canada, 2003)
Keywords: Arabes; Musulmans

Création d'un numéro de variétés suivie d'une réflexion sur l'évolution du travestisme à Montréal, de 1969 à 2000 - Gauthier, Ives (Université du Québec à Montréal, 2003)
Keywords: Théâtre

Les Yvettes comme l’expression d’un féminisme fédéraliste au Québec - Godin, Stéphanie (Université du Québec à Montréal, 2003)
Keywords: Féminisme

Le Montreal Council of Women / Conseil des Femmes de Montréal, de 1940 à 1967, à travers les questions de planification urbaine, d'immigration et des femmes dans le monde du travail - Hilairet, Sabine (Université d'Angers, 2003)
Keywords: Femmes; Féminisme; Montreal Local Council of Women; Travail

Le mouvement des femmes au Canada de 1970 à 2000: définir nos priorités - Kaye, Lynn; McDonald, Lynn (Madeleine Parent, militante, 2003)
Keywords: Femmes; Féminisme; Parent, Madeleine

SAINT-JEAN, IDOLA - Lavigne, Marie; Stanton-Jean, Michèle (Dictionnaire biographique du Canada, 2003)

Prendre et trouver sa place: discours hétéronormatifs et pratiques hétérosexuelles dans un cruising bar de Montréal - Lebrun, Aurélie (Université McGill, 2003)
Keywords: Alcool

Comment une militante a conquis le cœur des femmes immigrantes du Québec - Mulay, Shree (Madeleine Parent, militante, 2003)
Keywords: Parent, Madeleine

Femmes et changement social au Québec. L’apport de la jeunesse ouvrière catholique (1931-1966) - Piché, Lucie (Presses de l’Université Laval, 2003)
Keywords: Femmes; Jeunesse ouvrière catholique (JOC)

Female Skateboarders and their Negotiation of Space and Identity - Porter, Natalie Louise (Université Concordia, 2003)
Keywords: Femmes

Indispensable but not a Citizen: the Housewife in the Great Depression - Baillargeon, Denyse (Contesting Canadian Citizenship. Historical Readings, 2002)
Keywords: Crise; Famille; Femmes

Counting the Costs of Living: Gender, Citizenship, and a Politic of Price in 1940s Montreal - Fahrni, Magda (Canadian Historical Review, 2002)
Keywords: Alimentation; Femmes; Prix; Épicerie

Vers l’avenir. Québec Women’s Politics Between 1945 and 1967: Feminist, Maternalist and Nationalist Links - Gosselin, Cheryl A. (Université de Montréal, 2002)
Keywords: Femmes; Féminisme; Nationalisme

A Maternalist Organization in Quebec: The Fédération Nationale Saint-Jean-Baptiste and the Struggle for Women’s Suffrage - Hébert, Karine (Quebec since 1800: Selected Readings, 2002)
Keywords: Femmes; Fédération nationale Saint-Jean-Baptiste

''Don't Let Your Girlfriends Ruin Your Marriage'': Lesbian Imagery in Chatelaine Magazine, 1950-1969 - Korinek, Valerie Joyce (Rethinking Canada History. The Promise of Women's History, 2002)
Keywords: Femmes; Mariage

Les transformations identitaires de femmes immigrantes indiennes de religion hindoue vivant à Montréal - Ladouceur, Nadya (Université du Québec à Montréal, 2002)
Keywords: Femmes; Indiens

Visualising the History of Women at Eaton's, 1869 to 1976 - O'Donnell, Lorraine Frances (Université McGill, 2002)
This thesis examines the place of female customers and employees at the T. Eaton Company of Canada between 1869 and 1976. The central argument is that the word "witness" conveys well the nature of their place in this, one of the most important retail firms in Canadian history. Women were witnesses for the Eaton's and its development. They attested to and consolidated the company by collectively supporting it in huge numbers, whether as customers or personnel. Women were also key eyewitnesses of Eaton's, of its merchandise and marketing, its stores and catalogues. As the word "witness" suggests, visuality was central to women's central place. Women bought into the Eaton's buying and selling strategies that privileged appearances, and the company assumed and fostered this visually-centered role, helping to construct it and encouraging women to adopt it. The Introduction to the thesis reviews the substantial literature on the company's history. The main body of the thesis is divided in two. Part I examines the company's foreign activities and the role of women therein. Following a description of the firm's foreign buying system is an examination of three of its main regions: Japan, Europe and the U.S.A. The closer the region was to Canada, the more familiar it was to Eaton's, the more female Eatonians were employed there, and the more these women were able carve out a niche for themselves as expert witnesses like fashion buyers or fashion reporters. Part II discusses the place of women in the company's activities within Canada. First, it outlines the history of and tensions between the company's two main retail sites: stores and catalogues. While run by men, these sites were "spectacles of women" including salesclerks, mannequins and customers. Examples considered in depth are Eaton's catalogue covers and store displays for foreign goods and places. They privileged female imagery, a strategy meant to add value both to the merchandise and the (incomplet)
Keywords: Eaton; Femmes; Magasins

L’immigration féminine au Canada durant les années 1920: la mise en place d’une politique fondée sur le "genre" - Vallée, Marie-Hélène (Recherches féministes, 2002)
Keywords: Britanniques; Femmes

The Feminization of Clerical Work in Early Twentieth-Century Montreal - Boyer, Laura Kate (Université McGill, 2001)
Keywords: Femmes; Travail

Pratiques et stratégies spatiales des employées de bureau montréalaises dans un contexte de décentralisation économique - Chicoine, Nathalie (Institut national de la recherche scientifique et Université du Québec à Montréal, 2001)
Keywords: Femmes; Travail

Vive la Canadienne! Les représentations de l’identité féminine dans le défilé de la Saint-Jean-Baptiste à Montréal (1924-1961) - Demers, Michel (Université de Sherbrooke, 2001)
Keywords: Femmes; Saint-Jean-Baptiste (fête)

Under Reconstruction: the Family and the Public in Postwar Montréal, 1944-1949 - Fahrni, Magda (Université York, 2001)
Keywords: Famille; Guerre

La contestation des espaces gais au centre-ville de Montréal depuis 1950 - Guindon, Jocelyn M. (Université McGill, 2001)
Keywords: Police; Quartiers

Le maternalisme, une solution féminine à la Crise? La réponse de la Fédération nationale Saint-Jean-Baptiste - Hébert, Karine (Bulletin d'histoire politique, 2001)
Keywords: Crise; Fédération nationale Saint-Jean-Baptiste

Sebben che siamo donne (Although we are Women): a Comparative Study of Italian Immigrant Women in Post-War Canada and Australia - Iuliano, Susanna (Université McGill, 2001)
Understanding the lives of Italian women who migrated to Canada and Australia in the post-war period is the goal of this thesis. Although governments assigned women secondary roles as dependants and 'followers' in the migration process, I argue that Italian women were central, not marginal, to the migration and settlement experiences of Italian immigrants. By placing Italian women front and centre of this study, I contribute to a small but growing body of work that challenges the male-centred perspective of most literature on Italian-Canadian and Italian-Australian migration and ethnicity. This thesis is structured within a feminist framework and uses interdisciplinary methods to gather and interpret quantitative and qualitative information about the lives of Italian immigrant women in post-war Canada and Australia. Using government and church archives, personal interviews, ethnic newspapers, legal documents, marriage registers and participant observer fieldwork, I explore three major themes. Firstly, I examine Italian immigrant women's understanding of power relations within their homes and workplaces. Rather than cast women as either passive victims or all-conquering heroines, I present the complexity of the sources of power and weakness in immigrant women's lives. I argue that Italian immigrant women had to cope with exploitation and disadvantage because of their class, gender and ethnic status. However, they responded to these challenges with resistance and resilience, and were able to affect change and wield power within certain constraints. Secondly, I compare the experiences of migration and settlement for Italian immigrant women in Canada and Australia and show how women's experiences were united by common gender concerns. I found overwhelming similarities between the family lives and work experiences of Italian-Canadian and Italian-Australian immigrant women, and in the government policies and programs that attempted to direct their migration and settlement in the post-war period. Finally, I examine how Italian immigrant women helped to construct what it means to be 'Italian' in post-war Canada and Australia. I show how gender roles assigned to, and chosen by, Italian-Canadian and Italian-Australian women, served as boundary markers for ethnic difference. Perceived differences in attitudes towards waged work, mothering, family responsibilities and sexuality were used by Italian immigrant women to distinguish themselves as members of an ethnic collective. Lien avec Montréal - bien expliqué dans l'intro
Keywords: Femmes; Italiens

Manly Smokes: Tobacco Consumption and the Construction of Identities in Industrial Montreal, 1888-1914 - Rudy, Robert Jarrett (Université McGill, 2001)
This dissertation explores the cultural practice of smoking and its connection to social relations from the beginning of cigarette mass production in Montreal in 1888 to the First World War. It uncovers the norms of smoking etiquette and taste, their roots in gender, class and race relations and their use in reproducing these power relationships. It argues that these prescriptions reflected and served to legitimize beliefs about inclusion, exclusion and hierarchy that were at the core of nineteenth century liberalism. Liberal ideals of self-control and rationality structured the ritual of smoking: from the purchase of tobacco; to who was to smoke; to how one was supposed to smoke; to where one smoked. These prescriptions served to normalize the exclusion of women from the definition of the liberal individual and to justify the subordination of the poor and cultural minorities. Furthermore, even while these prescriptions were at their height, an emergent group of beliefs began to recast notions of respectable smoking around new ideals of speed and ungendered universality. This challenge was not only part of the transition from bourgeois to mass consumption, it was the roots of a transformation of the liberal order in the years previous to the First World War.
Keywords: Tabac

Montreal's Designing Women - s.a. (The Beaver, 2000)
Keywords: Confection; Femmes

Femmes de soir (théâtre); suivi de Contours: réflexion à partir du théâtre africain-américain - Amoni, Emmanuelle (Université du Québec à Montréal, 2000)
Keywords: Africains; Noirs; Théâtre

Contribution de l'Association pour les droits des gai(e)s du Québec (ADGQ) dans l'affirmation des gais au Québec: 1976-1988 - Arsenault, Mathieu (Bulletin d'histoire politique, 2000)

Feminist Historians and Family History in Canada in the 1990's - Bradbury, Bettina (Journal of Family History, 2000)
Keywords: Famille; Féminisme; Histoire; Historiens

La construction du père québécois: le discours du mouvement familial et l’expérience des pères, 1945-1965 - Duhaime, Vincent (Université de Montréal, 2000)
Keywords: Famille

Voices of Portuguese Immigrant Women - Januário, Ilda; Marujo, Manuela (The Portuguese in Canada: From the Sea to the City, 2000)
Keywords: Femmes; Portugais

Roughing It in the Suburbs. Reading Chatelaine Magazine in the Fifties and Sixties - Korinek, Valerie Joyce (Studies in Gender and History, 2000)
Keywords: Femmes; Féminisme

Days and Nights: Class, Gender and Society on Notre-Dame Street in Saint-Henri, 1875-1905 - Lord, Kathleen (Université McGill, 2000)
Keywords: Quartiers; Rues; Saint-Henri

Parrots, picnics and psychic phenomena: The feminism, nationalism and social reform of Eva Circé-Côté in Le Monde Ouvrier's Montreal, 1900-1940 - MacLean, Jenne (Queen's University, 2000)
Keywords: Circé-Côté, Éva; Féminisme; Journalistes; Monde ouvrier (Le); Nationalisme

Féminisme et mouvement des femmes au Québec. Un bilan complexe - Maillé, Chantal (Globe: revue internationale d’études québécoises, 2000)
Keywords: Femmes; Féminisme